Migrant Workers Communication Pattern - Utamidewi, Wahyu; Nursanti, Siti; Tayo, Yanti; Mayasari,; Abidin, Zainal (International Journal of Psychosocial Rehabilitation, 2020)
Mother is a female figure who is the main figure in the family, a problem that occurs when a housewife works as a female migrant worker abroad, causing communication patterns of communication with the family to be ineffective and no attention to children left behind, so that children do not get full love from his mother. To bridge so that children remain in protection and affection, then the obligations and responsibilities in caring for, educating, and raising children are left to the nuclear family and extended family. The purpose of the study was to construct family communication patterns with mothers who work as women workers in Banyumas Regency. This study uses a qualitative research method with a phenomenological approach, an approach that will look for motives, meanings, and communication patterns from informants based on their conscious experience. Theories used in this research are phenomenology, symbolic interactionism, and social reality construction. Determination of infroman with the snowball technique (snowball technique). Research location in Banyumas Regency. The results of this study show that communication patterns of errors against children can result in personal deviations such as materialistic children, delinquency of children, promiscuity of children, and other deviant behavior. Whereas communication patterns between fathers or husbands to overseas wives that are not intensively and effectively intertwined can lead to sharing problems in family relationships, such as divorce. This research is important to do because the family is the smallest part of an organization in the community.